Pesan Moral pada Film "Yu Wo Wakasuhodo No Atsui Ai" (Her Love Boils Bathwater) - Ardani, Delisa Ardani; Arfianty, Rani (Jurnal Pendidikan Bahasa Jepang Undiksha, 2024)
Moral messages are the core that guides and gives direction to ethical values in various stories, stories, or life experiences. This research aims to find out what are the moral messages contained in the movie "Yu Wo Wakasuhodo No Atsui Ai" or Her Love Boils Bathwater. The research method used is descriptive qualitative, while the research problem is reviewed from the documentation of images and words. The forms of moral messages found will be collected into image documentation and words. The results obtained are 7 moral messages that are in accordance with Suseno's theory (2007: 142-149), namely honesty, being yourself, responsibility, independence, moral courage, humility and crisis attitude. All moral messages contained in this study are not only obtained through formal education such as schools, but can also be obtained through the home environment, books, movies and fairy tales.